Agricoltura di montagna in divenire: Approcci alle sfide agroalimentari in Trentino - Alisia Tognon; Alessandro Gretter; Mattia Andreola; Alessandro Betta (Revue de Géographie Alpine)
The current paper belongs to a set of ongoing multi-scalar and trans-disciplinary research studies investigating potential approaches for regenerating rural areas in the Alpine areas of Italy, which have been suffering for years from underused phenomena (Balducci, 2019; Gretter et al., 2018a).The paper focuses mainly on the territory of the Autonomous Province of Trento to investigate how farmers face the current challenges in different ways while looking for sustainable and viable systems from the ecological and socio-economic perspectives (Bender & Haller, 2017). Trentino’s cultural context reflects a long tradition of specific law rules, which have granted a degree of self-government capabilities in various sectors such as territorial planning and land use policies, culture and school system, or social services (Gretter et al., 2018b).Rather than present specific results based on deep quantity-qualitative analysis, the goal of the manuscript is to overview the peculiar features of this alpine territory, opening a series of inputs of reflection and discussions. Some have already been locally activated, but most must be addressed in a broader and systemic approach, involving a more comprehensive series of stakeholders, moving from public authorities to citizens.In this manuscript, we highlight ongoing experiences that the Trentino Agro-food value chain faces today and how this impact the territory and its cultural landscapes’ preservation.